Ginger (Zingiber officinale) Mass Ratio on Physicochemical And Sensory Characteristics of Liang Tea - Surachman Surachman; Yohana Sutiknyawati Kusuma Dewi (Universitas Gorontalo, 2022)
The study aims to find out the effect of ginger mass ratio on the physicochemical and sensory characteristics of liang tea. The ingredients of liang tea was consisting of the leaves of D.chinensis, T.spathacea, O.vulgare, P.amaryllifolius, stem bark of secang woods (Caesalpinia sappan), midrib skin of lidah buaya (Aloevera chinensis) and rhizome of ginger with certain mass ratio. The treatment was in the form of mass ratio of liang tea and ginger rhizome powder (20:0; 20:1; 20:2; 20:3; 20:4; 20:5; 20:6; 20:7). Parameters to observed are physical characters include color, pH and chemical characters include qualitative phytochemical testing, vitamin C content, total phenol content, total flavonoid content and antioxidant activity with DPPH inhibitory activity and followed by sensory characteristic. The results showed that the formulation of the mass ratio of liang tea:ginger 20:0 possess the highest value on total phenolic content, flavonoid content and antioxidant activity (43.62 ± 5.64 mg GAE/g, 39.69 ± 1.32 mg QE/g and 56.02 ± 1.74 % respectively). The color value of tea which possess the highest phytochemical content and antioxidant activity are *L value (28.6±0), *a (4.1±0), *b (3.7±0), *c (5.5±0) and *h (42.35±0.14). Sensory characteristic showed that liang tea and ginger with mass ratio 20:0 was the best result, with colour value (3.93±0.91), flavor (3.57±0.94), taste (3.60±0.97), sweetness (3.77±0.97) and fondness overall (3.80±0.85) Based of the results of Index effectivity showed that liang tea and ginger with mass ratio 20:0 showed the best formulation as rich-antioxidant liang tea.